lncRNA HHIP-AS1 Promotes the Osteogenic Differentiation Potential and Inhibits the Migration Ability of Periodontal Ligament Stem Cells - Qianyi Qin; Haoqing Yang; Chen Zhang; Xiao Han; Jing Guo; Zhipeng Fan; Jie Guo (Stem Cells International)
Alveolar bone remodeling under orthodontic force is achieved by periodontal ligament stem cells (PDLSCs), which are sensitive to mechanical loading. How to regulate functions of PDLSCs is a key issue in bone remodeling during orthodontic tooth movement. This study is aimed at investigating the roles of lncRNA Hedgehog-interacting protein antisense RNA 1 (HHIP-AS1) in the functional regulation of PDLSCs. First, HHIP-AS1 expression was downregulated in PDLSCs under continuous compressive pressure. Then, we found that the alkaline phosphatase activity, in vitro mineralization, and expression levels of bone sialoprotein, osteocalcin, and osterix were increased in PDLSCs by HHIP-AS1. The results of scratch migration and transwell chemotaxis assays revealed that HHIP-AS1 inhibited the migration and chemotaxis abilities of PDLSCs. In addition, the RNA sequencing data showed that 356 mRNAs and 14 lncRNAs were upregulated, including receptor tyrosine kinase-like orphan receptor 2 and nuclear-enriched abundant transcript 1, while 185 mRNAs and 6 lncRNAs were downregulated, including fibroblast growth factor 5 and LINC00973, in HHIP-AS1-depleted PDLSCs. Bioinformatic analysis revealed several biological processes and signaling pathways related to HHIP-AS1 functions, including the PI3K-Akt signaling pathway and JAK-STAT signaling pathway. In conclusion, our findings indicated that HHIP-AS1 was downregulated in PDLSCs under compressive pressure, and it promoted the osteogenic differentiation potential and inhibited the migration and chemotaxis abilities of PDLSCs. Thus, HHIP-AS1 may be a potential target for accelerating tooth movement during orthodontic treatment.